Insect Pests of Exotic Pines in India - Singh, Pratap; Fasih, Massrat; Prasad, Ganga (Indian Forester, 1982)
Exotic pines are being planted on a large scale in the country. With all exotics we face problems from indigerous and introduced pests. By and large except for pine adelgid which got inadvertently introduced into the country sometime back, the exotic pines have no insect pest problems. The other insects recorded from them are casual feeders only. Most of them belong to the order Lepidoptera with lesser numbers in Coleoptera, Hemiptera, Orthoptera, Hymenoptera and Isoptera. Majority of them are defoliators. All of them are potential pests. To check further spread of the pine adelgid no vegetative material should be transported from one region to another. With the passage of time indigenous insects will adapt themselves to their new hosts or insects from their native homes are likely to gain entry in their new homes. Therefore, continued surveillance is necessary for detection of new pest introductions and pest build-up. Relatively insect free conditions of pines today should not lull foresters to compiacency so that they neglect plans for alternate species or for control measures when pest build-up takes place.